Congenital Urethral Fistula With Stricture of Glandular Urethra - Vishwa Nath Sahai Yadava; Ramesh Chandra; Ravindra Naih Sharma (Indian Journal of Plastic Surgery)
An extremely rare congenital abnormality of the urethra characterized by a congenital fistula and associated with a stricture of the glandular portion has been presented.